2015
DOI: 10.4049/jimmunol.1303126
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Opsonized Bacteria Evoke an Inflammatory Dendritic Cell Phenotype and Polyfunctional Th Cells by Cross-Talk between TLRs and FcRs

Abstract: During secondary immune responses, Ab-opsonized bacteria are efficiently taken up via FcRs by dendritic cells. We now demonstrate that this process induces cross-talk between FcRs and TLRs, which results in synergistic release of several inflammatory cytokines, as well as altered lipid metabolite profiles. This altered inflammatory profile redirects Th1 polarization toward Th17 cell responses. Interestingly, GM-CSF–producing Th cells were synergistically evoked as well, which suggests the onset of polyfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 49 publications
5
58
0
1
Order By: Relevance
“…In contrast, DCs stimulated with either TLR ligands or (complexed) IgG do not induces significant TNFα or IL‐23 release. This is in accordance with low mRNA transcription levels of these cytokines after binding to either TLRs or FcγRs .…”
Section: Tlrs and Fcrs Acting Together To Eradicate Infectionssupporting
confidence: 80%
See 2 more Smart Citations
“…In contrast, DCs stimulated with either TLR ligands or (complexed) IgG do not induces significant TNFα or IL‐23 release. This is in accordance with low mRNA transcription levels of these cytokines after binding to either TLRs or FcγRs .…”
Section: Tlrs and Fcrs Acting Together To Eradicate Infectionssupporting
confidence: 80%
“…Functional cross‐talk between cell surface‐expressed TLRs and FcRs does not require internalization as blocking internalization of IgG‐opsonized S. aureus with the actin‐polymerization inhibitor, cytochalasin, did not abrogate production of inflammatory cytokines (TNFα, IL‐1β, IL‐6, and IL‐23) . Similarly, when large IgG‐coated beads (too large to phagocytose) were used to stimulate DCs in combination with ligands for the cell surface‐expressed TLR 2, 4, or 5, enhanced cytokine production was still observed . Combining IgG‐coated beads with ligands for the intracellular TLR7/8 also induced synergistic release of TNFα , which further suggest that triggering of both type of receptors is sufficient to induce an inflammatory response, even in the absence of phagocytosis.…”
Section: Tlrs and Fcrs Acting Together To Eradicate Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine macrophages, FcγR‐mediated stimulation of MAPK pathways, particularly the activation of p42 MAPK (also known as ERK2) results in TNF synthesis . Furthermore, antibody‐opsonization of bacteria triggered toll‐like receptor signaling pathways through FcγR resulting in upregulation of various cytokines, including TNF in human dendritic cells . Thus, IgG‐opsonization of bacteria results in enhanced phagocytosis supporting both MR1‐presentation and an elevated production of TNF by monocytes, which in turn results in more efficient activation of MAIT cells.…”
Section: Discussionsupporting
confidence: 53%
“…Next, we investigated whether the enhanced MAIT cell activation by IgG‐opsonization was due to a better association of E. coli with different cell populations relevant for MAIT cell activation in PBMCs. We took advantage of previously described protocols used to measure bacterial uptake of FITC‐ or CFSE‐labeled bacteria (Supplementary figure 2a). Using CFSE‐labeled E. coli we found that the presence of hiNHS or Intratect increased the association of bacteria with PBMCs (Supplementary figure 2b).…”
Section: Resultsmentioning
confidence: 99%